Analytic vision of foresight planning in venezuelan public universities - Lucena López, Yamileth Pastora (Cuadernos de Administración, 2014)
This work sought to analyze the scope of foresight planning in managing Venezuelan public universities (VPU) within the context of the Universidad Centroccidental Lisandro Alvarado (UCLA), Universidad Nacional Experimental Francisco de Miranda (UNEFM), and Universidad Nacional Experimental del Táchira (UNET) information society. This was a documentary study with a bibliographic design, supported on the analytic method; the intentional simple was aimed at three VPUs with foresight plans. The techniques to gather information included bibliographic review, critical reading, and content analysis, among others. Through the results, it was concluded that the VPUs under study coincide in the key areas toward where their foresight plans are aimed: teaching, research, and outreach. Additionally, one of the challenges for them from the information society is the use of information and communication technologies (ICT) both in academic and administrative issues. Regarding this, foresight planning is viable in university management. Its reach is broad, considering the present to make future scenarios in agreement with the key areas. It was recommended to identify strategic and emergent aspects at the universities, specifically the domain of corporate information/knowledge and organizational management/strategic level within the foresight framework